EFEKTIFITAS PEMBERIAN PENYULUHAN KESEHATAN DENGAN MENGGUNAKAN MODUL ASI EKSLUSIF TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL - Visti Delvina; Lety Sari Rahayu (Maternal Child Health Care, 2021)
Breastfeeding is breastfeeding without other additional food and drink for babies, from zero to six months of age. During that time, tje baby is really not given other intakes, including water. Sungai full city is only as one of the cities in Jambi Province, with exclusive breastfeeding coverage is only around 66.8% which is far from the 80% expectation. Tanah Kampung Community Health Center in 2021. The type of reserach is Quasy Experimental, with the type of design being One Group Pre And Post-Test Design. The research location is at Tanah Kampung Puskesmas, Sungai Penuh City, when the research was  conducted on July 12-24 2021. With a sample of 31 pregnant women in the third trimester using random sampling technique and univariate and bivariate analysis with statistical test T-test. The researchinstruments used in the study were questionnaires and the Exclusive Breastfeeding module. From the result of the bivariate analysis using dependent t-test, it was found that . There was an effect before and afterthe provison of health counseling using the exclusive breastfeeding module on the knowledge of pregnant women in The Tanah Kampung Puskesmasworking area in 2021. With a p-value = 0.000 (p≤0 0.05) and there is an effect before and after the provision of health counseling using the exclusive breastfeeding module on the attitude of pregnant women in the Tanah Kampung Puskesmas working area in 2021. With a pvalue = 0.003 ((p≤0 0.05. The conclusion is that the provision of health education using the exclusive breastfeeding module is effective on the knowledge and attitudes of pregnant women. It is hoped that the provision of health eduaction can provide motivation and good knowledge for pregnant women. Keywords : Knowledge, attitude, health education, breastfeeding module exclusive.